Na we go shine: women's wellbeing, agency, and health seeking behaviours in southeastern Nigeria - Shroff, Farah M. C. (Frontiers in Global Women's Health, 2025)
ObjectivesPeer-reviewed literature on southeastern Nigerian women's health status is scant. This participatory action research project explored mental and physical health status issues within a sample population of childbearing women in Cross River State.MethodsWe conducted an initial study using the formal chieftaincy channels in villages and learned that those who expressed themselves were primarily men. We found that their concerns differed from those of women. We conducted this study in an attempt to hear from women about their health needs in the context of their lives. Local women carried out face-to-face interviews in their language with childbearing women in their community. We interviewed 70 women from ages 18–45 in 12 villages.Results/discussionMost participants had their own farms and grew rice, cassava and yam to feed their families. The majority of participants had not completed elementary school and had given birth to an average of 6 children, 4 of whom survived. Most of the women who were included in this study walked 6–8 h per day to retrieve drinking water. Their young children and babies often accompanied their mothers on these journeys. Participants reported that they had suffered from malaria, diarrhea, anemia, hernia, waist pains, cough, eye problems and continuous headaches. Traditional healers were their first choice for treatment, partly because of physical and financial accessibility and partly because of cultural resonance and positive outcomes.ConclusionDespite tremendous social, economic and political barriers, our participants generally reported a strong sense of well-being and had positive outlooks on their lives. We also interviewed 15 traditional healers to enhance the statements made by our female participants regarding their health-seeking behaviors.